Experience gained by the Polish Military Contingent of IRAK in the field of logistic support and preparation of military equipment - Piękoś Dominik J. (2023)
The aim of the article is to present the experience gained by the Polish Military Contingent in Iraq in the field of logistic support and preparation of military equipment. An additional goal is to present how the process of technical security of the Polish Armed Forces outside the country has evolved.